2017
DOI: 10.1186/s12889-017-4284-x
|View full text |Cite
|
Sign up to set email alerts
|

What could keep young people away from alcohol and cigarettes? Findings from the UK Household Longitudinal Study

Abstract: BackgroundAdolescents are vulnerable to risky behaviours that are likely to co-occur. We examined whether happiness, awareness of alcohol- or smoking-related harm or the size of friendship networks would be longitudinally associated with young people’s risky behaviours.MethodsWe used available cases (N=1,729) from adolescents aged between 10 and 15 who participated in waves 2 and 3 of the UK Longitudinal Household Study that has annually collected population representative data from 40,000 UK households. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
1
9
0
5
Order By: Relevance
“…In addition, exposure to antitobacco advertisements was the only preventative factor associated with cigarette smoking among South Korean adolescents. These results are comparable with those reported in a U.K. study (Cable et al, ), which showed that the primary factor associated with persistent non‐use of cigarette smoking among adolescents was awareness of cigarette‐related harm. In summary, interventions to educate students about the harm caused by cigarettes could help adolescents to keep away from cigarette smoking.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, exposure to antitobacco advertisements was the only preventative factor associated with cigarette smoking among South Korean adolescents. These results are comparable with those reported in a U.K. study (Cable et al, ), which showed that the primary factor associated with persistent non‐use of cigarette smoking among adolescents was awareness of cigarette‐related harm. In summary, interventions to educate students about the harm caused by cigarettes could help adolescents to keep away from cigarette smoking.…”
Section: Discussionsupporting
confidence: 89%
“…El‐Toukhy et al () showed that, in various ethnic groups (e.g., Asian, Hispanic, non‐Hispanic), younger adolescents (11–13 years of age) were more susceptible to smoking than older adolescents. During adolescence, peer networks and their influence have been identified as very important for both engaging in (Chung & Joung, ) and abstaining from (Cable et al, ) risk‐taking behaviors. The smoking behavior of close friends and friend‐related stress have been shown to be risk factors in cigarette smoking and the use of other substances (Chung & Joung, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 39% of those aged 11–13 never had an alcohol drink in 2003, compared with 48% in 2010 [ 38 ]. Among a cohort of 10 to 15 year olds, happiness and awareness of alcohol-harm was associated with not being initiated into alcohol use [ 39 ]. Increasing awareness of the harms of alcohol may have played an important role in decreasing alcohol consumption among young people and the general population [ 3 ].…”
Section: Discussionmentioning
confidence: 99%